Frequency-domain characteristics of aerodynamic loads of offshore floating vertical axis wind turbines. (1st October 2015) - Borg, M.; Collu, M.
Highlights: Study into unsteady floating vertical axis wind turbine aerodynamic loads. Assessed impact of platform motion on frequency-domain load characteristics. Maximum loads not significantly changed, but augmented in motion frequency regions. Additional considerations required during the design of floating system. Abstract: The re-emerging interest in vertical axis wind turbines for floating offshore applications has led to a need to investigate the relatively complex dynamics of such floating offshore structures. Through the use of a coupled model of dynamics this article investigates the frequency-domain characteristics of floating vertical axis wind turbine aerodynamic loads. The impact of platform induced motion on aerodynamic loads is discussed in detail, with results indicating an increase in aerodynamic loads of several orders of magnitude over the range of frequencies usually containing significant wave energy. The subsequent impacts of these observations on system component design are elaborated.